Construction of an ecological security pattern for the Guanzhong Plain urban agglomeration: Scale perspective and hierarchy demand - Ye, Hao; Song, Yongyong; Xue, Dongqian; Xia, Siyou; Tang, Yu; Zhang, Liwei (Frontiers in Environmental Science, 2023)
As areas of dense populations and high economic activity, urban agglomerations have driven an overall increase in economic efficiency; however, the associated ecological risks are becoming increasingly apparent. The construction of ecological security patterns (ESPs) is an important approach for ensuring the ecological security of urban agglomerations, thereby achieving coordinated development of society, economy and ecology. Previous studies on ESPs have rarely considered the demand for ecosystem services at multiple scales and have accordingly failed to accurately identify important ecological sources. Here, we propose a novel method based on multi-scale ecosystem service demand to identify ecological sources, selecting the Guanzhong Plain urban agglomeration (GPUA) as study area, we construct a resistance surface by comprehensively considering natural and anthropogenic disturbances. In addition, we performed minimum cumulative resistance and gravity modeling to obtain and classify ecological corridors. The results revealed that the ecological sources identified in this study can enhance the connectivity of the inner regions of the GPUA and the linkage between north and south ecological corridors. The ecological sources were found to be concentrated in the southern Qinling Mountains and mainly include woodland and grassland. Furthermore, we identified 121 potential ecological corridors, 47 ecological nodes, and 49 ecological breakpoints, and established that the extent of land with a high level of ecological security accounts for 21.98% of the entire regional area. This study offers a new perspective for ESPs construction, which can provide a scientific basis and policy guidance for the optimization of spatial structure and the maintenance of ecological security in ecologically fragile urban agglomerations.